Peningkatan Keterampilan Grammartical Melalui Jemuran Tenses Bagi Siswa Kelas XII Ips 3 SMA Negeri 4 Pontianak - Wijayanti, Fransiska Dwi Mulyani (Jurnal Pembelajaran Prospektif, 2016)
The purpose of this research was to improve students' grammartical skills through "clothesline tenses". Inspired by the natural resources-based West Kalimantan local knowledge, the researcher was constructing media "clothesline tenses" using batik scrap materials cloth stitching authentically from West Kalimantan. Teaching and learning using locally available,plentiful, cheap and effectiveresources provide a good chance for quality teaching. They bring to alive classroom instruction and make learning more exciting. This research reflected that the implementation of this teaching media has increased the studentsâ€™ grammartical mastery positively. Supporting the positive process resulted, the quantitative data also revealed that without using â€œclothesline tensesâ€, studentsâ€™ learning outcomes showed 39% while using â€œclothesline tensesâ€ increased to 88%. It can be concluded that the use of "clothesline tenses" can improve the studentsâ€™grammartical mastery, and attract students to make a lot of correct English sentences meeting the criteria Contextual Teaching and Learning (CTL).